The family physician as a primary care consultant - the Mossel Bay experience - Klaus B. von Pressentin; Kartik S. Naidoo; Louis S. Jenkins; Johann Schoevers (AOSIS, 2021)
The South African family physician (FP) is an expert generalist who has a number of roles to strengthen the district health system. A research study on FPs in district hospitals has previously demonstrated an impact; however, more evidence on impact in primary health care (PHC) is needed. By serving as a consultant for the PHC team, the FP may improve access to care, capacitate team members, enhance comprehensiveness of care, and improve coordination and continuity of care. This report narrates the story of how one of the FPs at a rural district hospital recorded his experience of being a consultant to the PHC team and was able to self-audit the experience. A self-designed audit tool analysed 1000 patient consultations with the FP and enabled a reflection on the coronavirus disease 2019 (COVID-19)-related changes to the consultant role. There was a clear need for FPs to consult patients with complex multi-morbidity and multifaceted psychosocial aspects to their illness, in consultation with their team members. Patients were referred to them by medical officers, other specialists, family medicine registrars, allied healthcare professionals and nurse practitioners. The FP's ability to strengthen the PHC service outside the district hospital may be enhanced by creating more FP posts at a subdistrict level to support high-quality, team-based primary care in line with the PHC policy directions.